2021
DOI: 10.1175/jcli-d-20-0312.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Surface Temperature Response to 11-Yr Solar Cycle Forcing Consistent with General Circulation Model Results

Abstract: The 11-year solar cycle is associated with a roughly 1Wm-2 trough-to-peak variation in total solar irradiance and is expected to produce a global temperature response. The sensitivity of this response is, however, contentious. Empirical best estimates of global surface temperature sensitivity to solar forcing range from 0.08 to 0.18 K [W m-2 ]-1. In comparison, best estimates from general circulation models forced by solar variability range between 0.03-0.07 K [W m-2]-1, prompting speculation that physical mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Our main result is that C3, C4 and C5 do not show many differences at the level of the solar minima (i.e. and supporting recent analysis (Schmutz, 2021;Amdur & Huybers, 2023). Finally, Figure A8 shows the TSI composite time series C3 and C4.…”
Section: Tsi Composite Including the Jtsim-dara Productsupporting
confidence: 86%
See 1 more Smart Citation
“…Our main result is that C3, C4 and C5 do not show many differences at the level of the solar minima (i.e. and supporting recent analysis (Schmutz, 2021;Amdur & Huybers, 2023). Finally, Figure A8 shows the TSI composite time series C3 and C4.…”
Section: Tsi Composite Including the Jtsim-dara Productsupporting
confidence: 86%
“…A comprehensive discussion of the robustness of these various methodologies is out of the scope of the presented work. Readers can refer to Dudok de Wit et al (2017); Scafetta and Willson (2019); ; Amdur and Huybers (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Amdur et al 55 considered the period 1959–2019, including Solar Cycle 24, without removing the nonlinear trend. The year 1959 is a solar max and 2019 a min, which by themselves include an imbedded trend from solar max to solar min.…”
Section: Methodsmentioning
confidence: 99%
“…The role of solar activity in affecting climate is one of the most debated aspects of global climate variability (Bard & Frank, 2006; Solanki, 2002). Although a growing body of research has found evidence of solar variability controlling or pacing climate (Anchukaitis et al., 2013; Bond et al., 2001; F. S. Hu et al., 2003; Wang et al., 2005), much research has also demonstrated the limited impact of these minor radiation fluctuations (Amdur et al., 2021; Chiodo et al., 2019). Further, solar irradiance has been used to detract from the influence of anthropogenic greenhouse gas forcing on climate (Meunier & Reis, 2015; W. Soon & Legates, 2013; W. W.‐H.…”
Section: Introductionmentioning
confidence: 99%